Application of an optimized modified stir bar with ZnS nanoparticles loaded on activated carbon for preconcentration of carbofuran and propoxur insecticides in water samples and their HPLC determination. Issue 43 (13th April 2016) - Pebdani, Arezou Amiri; Khodadoust, Saeid; Toori, Mehdi Akbartabar; Zarezade, Vahid; Talebianpoor, Mohammad Sharif
Abstract : In this study, the stir bar was coated with the ZnS-NPs loaded on activated carbon (ZnS-AC) as well as [EMIM][PF6 ] ionic liquid using sol gel technique was used for stir bar sorptive extraction (SBSE) of carbofuran and propoxur. Abstract : In this study, the stir bar was coated with ZnS-NPs loaded on activated carbon (AC) (ZnS-AC) as well as 1-ethyl-3-methylimidazolium hexafluorophosphate ([EMIM][PF6 ]) ionic liquid (IL) using a sol gel technique which was used for stir bar sorptive extraction (SBSE) of carbofuran and propoxur. The extracted analytes were then quantified by high performance liquid chromatography (HPLC) equipped with an ultra violet detector. The best extraction performance for carbofuran and propoxur was obtained through the optimization of the factors affecting SBSE including the pH of the sample solution, ionic strength, extraction time, volume of desorption solvent, desorption time, and stirring speed. The fractional factorial design (FFD) was used to find the most important factors, which were then optimized by the central composite design (CCD) and the desirability function (DF). Under the optimal experimental conditions, the proposed method has linear ranges over 0.002–30 μg mL −1 with detection limits of 0.0003–0.0005 μg mL −1 and good RSDs (and n = 6) of 3.3–4.5% with the enrichment factors (EFs) in the range of 75.6–81.6-fold for carbofuran and propoxur. The developed method has been successfully applied to the determination of two N -methylcarbamate in environmental water samples such as tap water, river water, and mineral water.